Incubation-time distribution in back-calculation applied to HIV/AIDS data in India - Arni S.R. Srinivasa Rao; Masayuki Kakehashi (Mathematical Biosciences and Engineering)
In this article, HIV incidence density is estimated from prevalencedata and then used together with reported cases of AIDS to estimate incubation-time distribution. We used deconvolution technique and maximum likelihoodmethod to estimate parameters. The effect of truncation in hazardwas also examined. The mean and standard deviation obtained with theWeibull assumption were 12.9 and 3.0 years, respectively. The estimationseemed useful to investigate distribution of time between report ofHIV infection and that of AIDS development. If we assume truncation,the optimum truncating point was sensitive to the HIV growth assumed.This procedure was applied to US data for validating the resultsobtained from the Indian data. The results show that method workswell.